The gray zones of medicine healers & history in Latin America - Armus, Diego 1953-; Gómez, Pablo F. (University of Pittsburgh Press, 2021)
Introduction / Diego Armus and Pablo F. Gómez -- Domingo de la Ascensión and the criollo healing culture of the seventeenth-century Caribbean / Pablo F. Gómez -- The curing world of María García, an indigenous healer in eighteenth-century Guatemala / Martha Few -- Calundu : a collective biography of spirit possession in Bahia, 1618-present / James H. Sweet -- Dorotea Salguero and the gendered persecution of unlicensed healers in early republican Peru / Adam Warren -- Pai Domingos : healing slavery in nineteenth-century Bahia, Brazil / João José Reis -- Mystic of medicine, modern curandero, and "médico improvisado" : Francisco I. Madero and the practice of homeopathy in rural Mexico at the turn of the twentieth century / Jethro Hernández Berrones -- Herbs, roots, amulets, and prayers in the practices of "Saint" Vicente and other healers in São Paulo in the 1910s / Liane Maria Bertucci -- Recognition without a diploma : the wanderings of the healer Indio Rondín in early twentieth-century Colombia / Victoria Estrada and Jorge Márquez Valderrama -- The miraculous Doctor Pun, Chinese healers, and their patients in Lima, 1868-1930 / Patricia Palma and José Ragas -- Stepping through a looking glass : the Haitian healer Mauricio Gastón on the Romana sugar mill in the Dominican Republic in 1938 / Alberto Ortiz Díaz -- Jesús Pueyo : the "modern Argentine Pasteur" of the 1930s and 1940s / Diego Armus -- Doña Hermila Diego : Zapotec healer, entrepreneur, social activist, media star in modern Mexico / Gabriela Soto Laveaga.
Enthält bibliographische Angaben und Index. - Includes bibliographical references and index
Keywords: Healers / Latin America / Biography; Medical personnel / Latin America / Biography; Traditional medicine / Latin America / History; Therapeutics / Latin America / History; Medical sciences / Latin America / History; Diseases and history / Latin America; Medicalization / Latin America